(untitled) (Research, Society and Development, 2025)
The palatogingival groove (PGS), also called the lingual root groove or distolingual groove, is a morphological alteration that occurs during tooth development, altering the structure from the cingulum of the dental element and extending towards the cementoenamel junction and, when not treated correctly, can progress to periodontitis. This study aimed to describe and report the consequences of the Palatogingival Groove (PGS), an anatomical anomaly that can compromise oral health if not correctly diagnosed. An integrative review of the literature was carried out using the PubMed and Google Scholar databases, including articles published between 2015 and 2025, in Portuguese and English, available in full. Although partially, it is concluded that the Palatogingival Groove is a rare anomaly that mainly involves the upper lateral incisors and that can cause serious periodontal and endodontic problems, even leading to tooth loss if there is no early and correct diagnosis.